Key Role for CRB2 in the Maintenance of Apicobasal Polarity in Retinal Pigment Epithelial Cells - Paniagua, Antonio E.; Segurado, Alicia; Dolón, Jorge F.; Esteve-Rudd, Julián; Velasco, Almudena; Williams, David S.; Lillo, Concepción (Frontiers in Cell and Developmental Biology, 2021)
Apicobasal polarity is essential for epithelial cell function, yet the roles of different proteins in its completion is not fully understood. Here, we have studied the role of the polarity protein, CRB2, in human retinal pigment epithelial (RPE) cells during polarization in vitro, and in mature murine RPE cells in vivo. After establishing a simplified protocol for the culture of human fetal RPE cells, we studied the temporal sequence of the expression and localization of polarity and cell junction proteins during polarization in these epithelial cells. We found that CRB2 plays a key role in tight junction maintenance as well as in cell cycle arrest. In addition, our studies in vivo show that the knockdown of CRB2 in the RPE affects to the distribution of different apical polarity proteins and results in perturbed retinal homeostasis, manifested by the invasion of activated microglial cells into the subretinal space. Together our results demonstrate that CRB2 is a key protein for the development and maintenance of a polarized epithelium